The German awakening: Protestant renewal after the enlightenment, 1815-1848 - Kloes, Andrew (Oxford studies in historical theology, 2019)
Inhaltsverzeichnis: The history of the concept of religious awakening in German Protestantism -- Religious enlightenment and awakening: historical consciousness and Protestant identity -- The awakening and preaching -- The awakening and theology -- The awakening and new religious societies for Evangelism -- The awakening and new religious societies for social reform.